(untitled) (Bangladesh Medical Journal, 2019)
Tubal rupture following an ectopic pregnancy is usually associated with profound hemorrhage which can lead to an unstable hemodynamic state that can risk the life of the patient. To explore the pattern of ruptured ectopic pregnancy in a secondary level healthcare facility, this Cross-sectional study was conducted among 100 ruptured ectopic pregnancy cases at 250 Bedded General Hospital, Tangail from January to November 2017. Cases were diagnosed by taking history (short period of amenorrhoea, acute lower abdominal pain and per-vaginal bleeding), clinical examination and relevant investigations (per-abdominal ultrasonography, TVS, CBC, serum ß-hCG level). Postoperatively, all the patients were followed up meticulously till discharge. The mean age of patients was 33.5(±7.8) years and the highest incidence (43%) was recorded in the age group of 26-30 years. All the patients were managed surgically with no record of case fatality. The most common site for the extra-uterine pregnancy was the tubal area (80%), 13% were ovarian pregnancy, 2% were abdominal and 5% were in other sites (rudimentary horn of uterus, cessarian scar). Chronic pelvic inflammatory disease was the most common risk factor (70%). Other risk factors such as, H/O receiving subfertility treatment (assisted reproduction/ ovulation inducing drugs), previous ectopic pregnancy, developmental errors of uterus, caesarean scar pregnancy and unknown cause were 10.0%, 6.0%, 3.0%, 3.0% and 8.0% respectively. The rise of serum ß-hCG level was found ≤1500 IU/L in 72% and >1500 IU/L in 28% of patients. Tubal area found to be the most common site of ruptured ectopic pregnancy in this study and chronic pelvic inflammatory disease was the most common risk factor followed by undergoing subfertility treatment. Surgical intervention was the choice of treatment in all cases with zero fatality recorded. Bangladesh Med J. 2019 May; 48 (2): 20-23